Diagnostic delay and out of pocket expenditure in extra pulmonary tuberculosis patients: a cross sectional study in DOTS centre of a tertiary care hospital in South India - K. V., Manikanta; Gowda, Sudhir; B. R., Harish; V., Ariptha (International Journal Of Community Medicine And Public Health, 2022)
Background: Extra pulmonary tuberculosis (EPTB) accounted for 15% of the cases. Diagnosing EPTB is challenging as it frequently has non-specific clinical presentation and it may simulate other conditions, which may contribute towards delay in diagnosis. Delay in diagnosis and treatment could lead to increased disease severity, increased complications and economic burden for the patient and the families affected. Methods: This Descriptive cross-sectional study was conducted in directly observed therapy short-course (DOTS) center, Mandya institute of medical sciences (MIMS), India. Patients who are diagnosed with EPTB with age > 18 years were selected, informed consent was taken from 60 patients before collecting data. Data was analysed using Epi-Info (version 3.5.1) software. Descriptive statistics like mean, standard deviation and proportion are used Results: Of the 60 patients, majority 76.7% were in the age group 18-45 years, 68.3% were male, 75% from rural background and 55% belonged to class III socioeconomic status. Statistically significant diagnostic delay was seen with respect to female sex (total delay = 75.1±9.1 days), age group 18 to 30 years (74.5±5.1 days), lower socio-economic status (74.0±4.5 days), negative HIV status (72.7±4.4 days) and site of tuberculosis. Out of pocket expenditure was significantly higher in male sex (Rs. 22,839.0±5,174.7), age group more than 45 (Rs. 34,335.7±5,134.1) and among higher socioeconomic status Conclusions: Many EPTB patients, presenting to DOTS center, experience a long delay in the initiation of treatment, particularly patients with TB lymphadenitis. The patient delay is the major contributor to the total delay.